An investigation into how Web 2.0 can be harnessed to create value for the customer and enterprise, both in the present and the near future - Vijayaratnam, Niko Alistair (2007)
The term Web 2.0 is currently in vogue, is subject to enormous volumes of hype, and has been heralded as a business revolution [...] caused by the move to the Internet as a platform (O'Reilly, 2006). However you interpret the meaning of the term, the truth is that killer Web 2.0 applications are changing the way that we interact with the Internet and each other, causing certain businesses to rethink their existing business models. As such Web 2.0 is having a noticeable and sometimes disruptive impact on the way businesses are operating today. In an effort to understand the rules for success on this new Web platform, this dissertation engages in case study analyses of three prominent Web 2.0 products and services in conjunction with research into the current addressable markets and technologies that are pertinent to the topic. The research highlights interesting similarities between each of the chosen web 2.0 companies and indicates that the convergence in digital content, distribution channels and technology is a key factor driving forward the uptake of Web 2.0 products. Finally, this dissertation establishes that in fact Web 2.0 is still far from perfect and that the next iteration of the Web is likely to have just as profound an impact upon our lives as Web 2.0 has done to date.